THE RESEARCH ON INNOVATIVE APPLICATION OF ZHUANG BROCADE PATTERN FROM GUANGXI IN CONTEMPORARY TEXTILES - Zhu, Geli; Khiaomang, Kriangsak (Fine Arts Journal: Srinakharinwirot University, 2025)
Background and Objectives: The Guangxi Zhuang Autonomous Region, located in southern China, is home to various ethnic minority groups. The Zhuang ethnic group, the largest ethnic minority in China, possesses a rich and enduring cultural history, particularly reflected in their traditional textile art. Zhuang brocade is recognized as one of the four most renowned brocades in China, with its distinctive patterns and embedded cultural meanings making it highly significant in terms of culture, technology, aesthetics, and social value. This research aims to deeply explore the history and cultural diversity of the Zhuang people in Guangxi through literature review and field research. It also seeks to analyze the production processes and artistic characteristics of Zhuang textiles, as well as investigate how traditional Zhuang patterns can be integrated into contemporary design concepts. Methods: The study utilizes documentary research by collecting and reviewing a wide range of sources relevant to the thesis topic, including academic articles, research papers, books, and both domestic and international scholarly literature. Comparative analysis was conducted to examine the distinctive patterns of the Zhuang people in Guangxi. In addition, field research methods were employed, combining theoretical concepts with practical implementation through observation, empirical data collection, statistical recording, photography, and detailed visual documentation. Key Findings: The study found that the design, color schemes, and patterns of Zhuang textiles are deeply influenced by Zhuang culture and reflect national history and aesthetic philosophies. The research also explored the integration of traditional Zhuang textile patterns into contemporary design through the creation of the collection “Butterfly Rhythm of Zhuang Township.” This contemporary textile collection, designed by the researcher, demonstrates the potential for cultural application and artistic value in modern textile design. It contributes to the preservation and innovation of Zhuang culture while meeting contemporary aesthetic standards and market demand. Implications of the Study: Zhuang weaving is a traditional craft with profound historical and cultural significance. Its unique patterns and artistic features make it an important part of ethnic cultural heritage. The intricate and precise production techniques reflect the exceptional skill of Zhuang artisans, with each step in the weaving process acting as a vessel for transmitting traditional knowledge and cultural identity. Zhuang textiles not only embody craftsmanship but also serve as a cultural and historical medium. Conclusions and Future Study: The integration of traditional Zhuang textile patterns from Guangxi into contemporary textile design reflects a fusion of culture and innovation. This demonstrates the potential for future product development and highlights a promising direction for further exploration and experimentation. Expanding the use of Zhuang textiles requires innovation and integration, with an emphasis on preserving regional and cultural identity. Blending traditional patterns with modern design elements can result in culturally meaningful works that also possess distinct regional characteristics.